Analysis of the TGT Cooperative Learning Model in Physics Learning: In Terms of The Implementation of Procedures and Principles - Alfajri Adha; Affan Rera; Salman Al Farisi (International Journal of Education and Teaching Zone)
This study aims to analyze the implementation of procedures and principles in the TGT type cooperative learning model used by MAN 1 Jambi City teachers in learning Physics. This type of research is descriptive qualitative research. The subject of this research is the Physics teacher of MAN 1 Jambi City. The method used in collecting data is interview. The results showed that the implementation of the procedure was according to the syntax of the TGT type cooperative model in the Good category with an average value of 3 . The principles that the teacher most often uses in the TGT type cooperative learning model are group discussions in the Fairly Good category with a percentage score of 38.4%.